Islam dan Adat dalam Tradisi Perkawinan Masyarakat Suku Bugis: Analisis Interaksionisme Simbolik - Abd. Sattaril Haq (AL-HUKAMA, 2020)
This article is intended to examine the relationship between Islam and adat in the Bugis traditional wedding procession by using symbolic interactionism analysis. The procession of the Bugis traditional wedding tradition is divided into several parts, namely mappese-pese or mabbaja laleng which is interpreted as a process to find out whether the couple to be married has a fiance or not, this is intended as a form of caution not to propose to a woman who has been proposed. by other people. Madduta is done as a form of appreciation or love among humans. Mappettu ada is meant to reinforce the outcome of the conversation and is intended to elevate the position of women in the procession. Mappacci is meant to carry out the self-cleaning process by using several traditional instruments and using the Koran and praise to the Prophet in the form of reading barazanji as its main foundation and giving leko' is meant as a form of husband's responsibility in providing for his wife. This gives legitimacy that Islam and customs in the tradition of Bugis marriage go hand in hand or a form of acceptance of the Bugis community with Islamic values described in the traditions being carried out.